Differential stability of Gcn4p controls its cell-specific activity in differentiated yeast colonies - Váchová, Libuše; Plocek, Vítězslav; Maršíková, Jana; Rešetárová, Stanislava; Hatáková, Ladislava; Palková, Zdena (mBio, 2024)
Gcn4p belongs to conserved AP-1 transcription factors involved in many cellular processes, including cell proliferation, stress response, and nutrient availability in yeast and mammals. AP-1 activities are regulated at different levels, such as translational activation or protein degradation, which increases the variability of regulation under different conditions. Gcn4p activity in unstructured yeast liquid cultures increases upon amino acid deficiency and is rapidly eliminated upon amino acid excess. Gcn2p kinase is the major described regulator of Gcn4p that enables GCN4 mRNA translation via the uORFs mechanism. Here, we show that Gcn4p is specifically active in U cells in the upper regions and inactive in L cells in the lower regions of differentiated colonies. Using in situ microscopy in combination with analysis of mutants and strains with GFP at different positions in the translational regulatory region of Gcn4p, we show that cell-specific Gcn4p activity is independent of Gcn2p or other translational or transcriptional regulation. Genetically, biochemically, and microscopically, we identified cell-specific proteasomal degradation as a key mechanism that diversifies Gcn4p function between U and L cells. The identified regulation leading to active Gcn4p in U cells with amino acids and efficient degradation in starved L cells differs from known regulations of Gcn4p in yeast but shows similarities to the activity of AP-1 ATF4 in mammals during insulin signaling. These findings may open new avenues for understanding the parallel activities of Gcn4p/ATF4 and reveal a novel biological role for cell type-specific regulation of proteasome-dependent degradation.IMPORTANCEIn nature, microbes usually live in spatially structured communities and differentiate into precisely localized, functionally specialized cells. The coordinated interplay of cells and their response to environmental changes, such as starvation, followed by metabolic adaptation, is critical for the survival of the entire community. Transcription factor Gcn4p is responsible for yeast adaptation under amino acid starvation in liquid cultures, and its activity is regulated mainly at the level of translation involving Gcn2p kinase. Whether Gcn4p functions in structured communities was unknown. We show that translational regulation of Gcn4p plays no role in the development of colony subpopulations; the main regulation occurs at the level of stabilization of the Gcn4p molecule in the cells of one subpopulation and its proteasomal degradation in the other. This regulation ensures specific spatiotemporal activity of Gcn4p in the colony. Our work highlights differences in regulatory networks in unorganized populations and organized structures of yeast, which in many respects resemble multicellular organisms.
Keywords: proteolýza; differentiated colonies; proteosyntéza; Saccharomyces cerevisiae Proteins; Basic-Leucine Zipper Transcription Factors; spatially structured populations; stabilita proteinů; yeast; Saccharomyces cerevisiae; Protein Stability; Protein Serine-Threonine Kinases; proteasomal degradation; Protein Biosynthesis; Gene Expression Regulation, Fungal; regulace genové exprese u hub; transkripční faktory bZIP; cell-specific regulation; Saccharomyces cerevisiae - proteiny; transcription factor; protein-serin-threoninkinasy; Proteolysis